Aportes bibliométricos à produção científica nos principais periódicos da área de Ciência da Informação no Brasil, no período de 2006-2010 - Alves, Bruno Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Bibliometric studies constitute a set of procedures which analyzes the behavior of recorded information through indicators that use measurements, statistical analyzes and technological resources, aiming to examine and assess the production of information in different knowledge areas. Among the indicators used, the ones on scientific collaboration are highlighted. Scientific collaboration has been defined as two or more actors working in partnership, sharing information and knowledge. This research aimed to map the scientific collaboration networks using articles from Information Science journals in Brazil in the period from 2006 to 2010. More specifically, this study sought to identify the communities that are formed from the thematic affinities and relationships established through co-authorship, examining them in the national and/or international context, with emphasis on the most productive authors in different themes which contribute to the construction of scientific knowledge in the area of Information Science. As for research procedure, all articles published were collected, from a total of 605 articles, in the following journals: Ciência da Informação, DataGramaZero, Perspectivas em Ciência da Informação, Informação & Sociedade: Estudos e Transinformação. A qualitative analysis of the obtained information was performed by mapping how knowledge is being constructed in the area of Information Science. Excel Software was used for organizing the information and Pajek Software for constructing scientific collaboration networks. Indicators of network were calculated - density and degree centrality for author cooperation network, as well as density, degree centrality and betweenness centrality for institutional collaboration network - using Ucinet Software to provide analysis and more accurate deepening of the existing inter-relations among... (Complete abstract click electronic access below)

Os estudos bibliométricos constituem um conjunto de procedimentos que analisa o comportamento da informação registrada, por meio de indicadores que utilizam as quantificações, análises estatísticas e recursos tecnológicos, com o objetivo de analisar e avaliar a produção da informação nas diferentes áreas do conhecimento. Dentre os indicadores utilizados, destacam-se os de colaboração científica que tem sido definida como dois ou mais atores trabalhando em parceria, onde compartilham informação e conhecimento entre si. Esta pesquisa objetivou mapear as redes de colaboração científica, utilizando os artigos dos periódicos da área de Ciência da Informação, no Brasil, no período de 2006 – 2010. De forma mais específica, pretendeu-se identificar as comunidades que se formam a partir das afinidades temáticas e das relações estabelecidas pelas coautorias, examinando-as em âmbito nacional e/ou internacional, com destaque para os autores mais produtivos, nas diferentes temáticas, que contribuem para a construção do conhecimento científico na área de Ciência da Informação. Como procedimento de pesquisa, realizou-se um levantamento de todos os artigos publicados, em um total de 605 artigos, nos seguintes periódicos: Ciência da Informação, DataGramaZero, Perspectivas em Ciência da Informação, Informação & Sociedade: Estudos e Transinformação. Realizou-se uma análise qualitativa das informações obtidas, a partir de um mapeamento de como está sendo construído o conhecimento na área de Ciência da Informação. Utilizaram-se o Software Excel, para organização, e o Software Pajek, para a construção das redes de colaboração científica. Foram calculados os indicadores de rede – densidade e grau de centralidade para rede de colaboração entre autores, densidade...
Keywords: Bibliometric studies; Bibliometria; Ciência da informação - Periódicos - 2006-2011 - Brasil; Co-autoria; Redes de informação; Cooperação intelectual; Analise multivariada